The impact of Agile Manufacturing on Achieving Competitive Advantage/ Analytical Research of Sample Views of A Sample of Officials of the Productive Departments of the General Company for the Automotive Industry / Alexandria - Mohammed abdu.lkadhim, Ali (Iraqi Journal for Administrative Sciences, 2024)
This research seeks to determine the role played by the effect of Agile Manufacturing in achieving the competitive advantage by application in the company in question and for that the dimensions of Agile Manufacturing : changing systems, information, cooperation, as an independent variable ، And the competitive advantage : cost, flexibility, quality, delivery as the approved variable and this research was tested in the manufacturing sector choosing a sample of the company’s employees the most important conclusions is the availability Agile manufacturing variable in the company under study in all its dimensions, this is a good indicator that shows what the company shows towards embracing manufacturing strongly among competitors, as well as the application of the decentralization policy As for the most important recommendations it was necessary to make sure to make the Agile manufacturing philosophy and competitive advantage among the priorities that define the scope of the organization's importance.